Lyme Disease: Knowledge and Practices of Family Practitioners in Southern Quebec - Cécile Ferrouillet; François Milord; Louise Lambert; Anne Vibien; André Ravel (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Public health authorities in Quebec have responded to the progressive emergence of Lyme disease (LD) with surveillance activities and education for family physicians (FPs) who are key actors in both vigilance and case management.